The Role of Social Media in Building Trust, Creativity, and Satisfaction for Millennial Entrepreneurs - Arifin Djakasaputra; M. Tony Nawawi (Sultan Publisher, 2024)
This research aims to investigate the role of social media in enhancing trust, self-perceived creativity, and satisfaction among millennial entrepreneurs. In general, the data was collected through sampling from mineral entrepreneurs in Jakarta. Where data collection is done by distributing questionnaires. The data was analysed using partial least squares structural equation modelling. Finally, the research results show that social media marketing activities have a positive and significant impact on trust, social media marketing activities have a positive but not significant effect on self-perceived creativity, trust has a positive but not significant impact on self-perceived creativity, and trust has a negative and significant impact on entrepreneurial satisfaction. This research can contribute to marketing experts and millennial entrepreneurs in enhancing the quality of advertising information and the credibility of social media used to support creativity, trust, and satisfaction. Furthermore, marketing experts and millennial entrepreneurs with online-based communities should optimize their marketing activities on social media.